Technology adoption, social learning, and economic policy - Paul Heidhues; Nicolas Melissas (European School of Management and Technology (ESMT), 2010)
We study a two-player dynamic investment model with information externalities and provide necessary and sufficient conditions for a unique switching equilibrium. Within this setup, we ask whether policymakers should interfere when better informed agents make individual investment decisions. We find that when the public information is sufficiently high and a social planer therefore expects an investment boom, investments should be taxed. Conversely, any positive investment tax is suboptimally high if the public information is sufficiently unfavorable. We also show that an investment tax may increase overall investment activity.
urn:nbn:de:101:1-201106143718
Keywords: D62; D83; 650; information externality; strategic waiting; delay; information cascade; investment boom; optimal taxation; Innovationswettbewerb; Informationsverbreitung; Externer Effekt; Betriebliche Investitionstheorie; Optimale Besteuerung